Effect of magnetic field on hysteretic characteristics of silicon diodes under conditions of low-temperature impurity breakdown - Aleinikov, A.B.; Berezovets, V.A.; Borblik, V.L.; Shwarts, M.M.; Shwarts, Yu.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Effect of magnetic field (up to 14 T) on current-voltage characteristics of silicon n⁺ -p diodes which manifests hysteresis loops related with low-temperature impurity breakdown has been studied. With growth of magnetic field, the hysteresis loops are narrowed and decreased in amplitude and then disappear, but the breakdown continues in a soft form. Planar design of the diode has allowed separating the influence of magnetic field on mobility of the carriers executing impact ionization of the impurities and on the ionization energy itself. Theoretical analysis of the experimental data permitted us to determine the dependence of the ionization energy on the magnetic field. As in other investigated semiconductors, our results demonstrate the dependence of B¹/³ type. A model capable to explain qualitatively the mechanism of suppression of the hysteresis loops by magnetic field is proposed as well.